Pulse laser generation using Mxene / max phase as saturable absorber / Hissah Saedoon M Albaqawi - Hissah Saedoon , M Albaqawi (2022)
Optical fiber lasers have drawn a lot of researchers’ interest and attention in recent years particularly as sources for laser signals. This could be attributed to its number of significant advantages, such as more compact and robust form factors as well as being significantly less costly to build and operate as compared to their conventional bulk laser counterparts. Moreover, the utilisation of fiber laser provides much more flexibility in terms of design and usage of the laser. While optical fiber lasers are highly suited for applications that require relatively low laser powers, they are generally not used for applications requiring higher powers. This is because in most cases, optical fiber lasers operate in a continuous wave (CW) mode at low powers. In order to overcome this limitation, significant efforts have been made to increase the output power of optical fiber lasers by pulsing, allowing them to accumulate power before discharging the energy as a lasing signal. Pulsing in an optical fiber can be realised through multiple techniques, with Q-switching and mode-locking being the most common and both techniques can be further classified as either active or passive systems. In the present study, passively Qswitched and mode-locked pulse lasers has been achieved through the use of saturable absorbers (SA) namely Ti3AlC2 MAX phase and Ti3C2Tx MXene. Both materials were chosen as the SA materials because they possess good optoelectronic and optical properties such as high damage thresholds and modulation depth. Besides that, they also exhibit nonlinear saturable absorption and increased transmittance at higher light fluences, which is useful especially for mode-locking in fiber-based femtosecond lasers. Initially, Ti3C2Tx MXene was synthesized from Ti3AlC2 MAX phase by etching with a mixture of lithium fluoride (LiF) and hydrochloric acid (HCl) to remove the aluminium (Al) layers from the Ti3AlC2 MAX phase. Two different structures of SA, namely polyvinyl alcohol (PVA) thin film and side-polished fiber (SPF), were examined for their potential in the generation of pulse laser. The erbium-doped fiber (EDF) and thuliumholmium co-doped fiber (THDF) serve as the gain medium in which EDF is capable of amply light efficiently within the region of 1550 nm wavelength, whereas the trivalent thulium-holmium ions (Tm3+ - Ho3+) have emerged as a promising rare-earth ion that has a radiative transition within the 2.0 μm wavelength region. Based on the experiment conducted in this study, it has been proven that the proposed systems were able to generate Q-switching and mode-locking operation at the 1.5 μm and 2.0 μm wavelength regions. The generated outputs indicated that the Ti3AlC2 MAX phase and Ti3C2Tx MXene based SA can induce high quality and stable Q-switched and mode-locked pulses in the EDF and THDF laser cavity, thus have significant contributions and uses in several fields of photonics applications.